Handbook of international advertising research - Cheng, Hong, 1958- (Chichester : Wiley-Blackwell, 2014)
This timely handbook brings academic excellence to international advertising research in the form of 28 contributions from over 40 leading scholars. The handbook's comprehensive treatment highlights existing knowledge, reports major findings across the subject, and recommends directions and agendas for future research. It fills the existing gap between the rapid growth in scholarly research on international advertising and the pressing need for more high-quality research in the area. It covers 28 major areas in international advertising research, with contributions from more than 40 international advertising scholars based in over 10 countries or territories. Comprehensive treatment includes the history of international advertising, audiences and media, strategy and execution, content effects, regulation, ethics, and advertising education. The book highlights existing knowledge in international advertising, reports major findings on a broad range of topics, and offers expert recommendations on directions for future research. Contributors represent the most highly respected academics among international advertising researchers.
Includes bibliographical references and indexes.
Print version record.
Keywords: Advertising -- Research; BUSINESS & ECONOMICS -- Advertising & Promotion; Advertising -- Research; Electronic books